IMPLEMENTASI KEBIJAKAN PROGRAM PEMBERDAYAAN MASYARAKAT PESISIR (PEMP) DI KABUPATEN KUPANG - Umbu T W Pariangu (Universitas Nusa Cendana, 2020)
This research seeks to see and decrypt the extent to which the implementation of coastal communityempowerment programs in Kupang regency has an impact on community empowerment and welfare.Based on the variables of planning, implementation, utilization of programs and monitoring andevaluation, resulting in the findings that support for PEMP program is moderate. The obstacles tothe implementation of PEMP are the lack of community resources in the implementation of theprogram and the lack of effectiveness in the technical program manager performance. This hasimplications for the weak impact of PEMP program policy in a broader way for the economy andcommunity empowerment of Kupang Regency. Keywords: Policy Implementation, Community Empowerment